Responses of a Natural Phytoplankton Community From the Drake Passage to Two Predicted Climate Change Scenarios - Pausch, Franziska; Koch, Florian; Hassler, Christel; Bracher, Astrid; Bischof, Kai; Trimborn, Scarlett (Frontiers in Marine Science, 2022)
Contrasting models predict two different climate change scenarios for the Southern Ocean (SO), forecasting either less or stronger vertical mixing of the water column. To investigate the responses of SO phytoplankton to these future conditions, we sampled a natural diatom dominated (63%) community from today’s relatively moderately mixed Drake Passage waters with both low availabilities of iron (Fe) and light. The phytoplankton community was then incubated at these ambient open ocean conditions (low Fe and low light, moderate mixing treatment), representing a control treatment. In addition, the phytoplankton was grown under two future mixing scenarios based on current climate model predictions. Mixing was simulated by changes in light and Fe availabilities. The two future scenarios consisted of a low mixing scenario (low Fe and higher light, low mixing treatment) and a strong mixing scenario (high Fe and low light, strong mixing treatment). In addition, communities of each mixing scenario were exposed to ambient and low pH, the latter simulating ocean acidification (OA). The effects of the scenarios on particulate organic carbon (POC) production, trace metal to carbon ratios, photophysiology and the relative numerical contribution of diatoms and nanoflagellates were assessed. During the first growth phase, at ambient pH both future mixing scenarios promoted the numerical abundance of diatoms (~75%) relative to nanoflagellates. This positive effect, however, vanished in response to OA in the communities of both future mixing scenarios (~65%), with different effects for their productivity. At the end of the experiment, diatoms remained numerically the most abundant phytoplankton group across all treatments (~80%). In addition, POC production was increased in the two future mixing scenarios under OA. Overall, this study suggests a continued numerical dominance of diatoms as well as higher carbon fixation in response to both future mixing scenarios under OA, irrespective of different changes in light and Fe availability.